2012
DOI: 10.5090/kjtcs.2012.45.4.242
|View full text |Cite
|
Sign up to set email alerts
|

Result of Surgical Resection for Pulmonary Metastasis from Urothelial Carcinoma

Abstract: BackgroundTreatment of pulmonary metastasis from urothelial cell carcinoma has been mostly palliative chemotherapy and the role of pulmonary metastasectomy has not been investigated much.Materials and MethodsThis study is a retrospective interim review of pulmonary metastasectomy from urothelial carcinoma at single institution between 1998 and 2010. Overall 16 patients underwent pulmonary metastasectomies.ResultsThere was no postoperative complication or hospital mortality. Mean hospital stay was 6 days. Overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 8 publications
0
12
0
3
Order By: Relevance
“…As described above, since the first promising study by Cowles et al [ 17 ], visceral metastasectomy has been offered to selected patients. Table 2 summarizes the outcomes of metastasectomy for visceral organs [ 18 28 ]. For example, Siefker-Radtke et al [ 18 ] reported the outcomes of 31 metastatic urothelial carcinoma patients treated with metastasectomy between 1985 and 2001.…”
Section: Resection Of Visceral Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…As described above, since the first promising study by Cowles et al [ 17 ], visceral metastasectomy has been offered to selected patients. Table 2 summarizes the outcomes of metastasectomy for visceral organs [ 18 28 ]. For example, Siefker-Radtke et al [ 18 ] reported the outcomes of 31 metastatic urothelial carcinoma patients treated with metastasectomy between 1985 and 2001.…”
Section: Resection Of Visceral Metastasismentioning
confidence: 99%
“…They observed a median of 5-year survival in six patients after the removal of a solitary lung metastasis without systemic chemotherapy. Since then, surgical consolidation for visceral metastases has also been performed in selected patients, and its beneficial role was anecdotally reported [ 18 28 ]. In the present study, we reviewed the current evidence in terms of an aggressive surgical approach to advanced urothelial carcinoma, and summarized the present recommendations regarding decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…12 There is minimal, high-quality data evaluating the role of metastasectomy in urothelial carcinoma (Table 3). [5][6][7][8][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] A recent Surveillance, Epidemiology and End Results-Medicare study evaluating survival outcomes for 497 patients with metachronous metastases who underwent metastasectomy found poor median OS of 19 months and 3-year survival of 38% compared with a median OS of 7 months in the synchronous metastasectomy group in the present study. 5 This difference might reflect the difference in tumor biology and disease burden at the time of metachronous versus synchronous metastases.…”
Section: Discussionmentioning
confidence: 76%
“…3,4 In an effort to prolong survival, some clinicians have used upfront surgery or consolidative metastasectomy after chemotherapy to treat single or oligometastatic disease in select patients (Table 4). [6][7][8][10][11][12][13] The outcomes were variable; TTP ranged from 7 to 18 months and OS from 14 to 52 months, which represents various patient populations and disease characteristics. In our present study, the median OS after metastasectomy was 30.0 months, which is comparable with those of previous studies on metastasectomy and is longer than that of patients who were mainly treated using systemic chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…After the initial report, there have been anecdotal reports that suggested the potential benefit of metastasectomy on survival of patients with urinary tract cancer. [6][7][8][9][10][11][12][13] However, because of the rarity of oligometastases associated with advanced urinary tract carcinoma eligible for surgical intervention, little is known about the efficacy of metastasectomy and prognostic factors affecting time to disease progression (TTP) and OS.…”
Section: Introductionmentioning
confidence: 99%